A REVIEW OF MATERIAL COVER FEATURES FOR MITIGATING URBAN HEAT ISLAND - Sri Novianthi Pratiwi (International Journal on Livable Space, 2018)
AbstractUrban Heat Island (UHI) is related to the increase of urban compared to rural temperature as the result of global phenomenon. The increase of temperature is predicted to be intensified along with the extend of urban activity in the near future. Therefore, the discussion on UHI becomes significance. This paper discusses the result of literature studies on thermal characteristics of materials that potentially used to reduce Urban Heat Island, especially in utilizing pavement and roof cover.  The result of the study concludes that the reduction of UHI is determined by: 1) the high-level albedo (the ratio between the reflected heat and the absorbed heat) of material that is influenced by the color and texture of its surface; 2) The high level thermal emittance of material; 3) The lower capacity of material to store the heat. 4) The capability thermal conductivity of material surface. Recommended pavements to reduce UHI are cool pavement, reflective pavement, porous pavers, permeable pavers, pervious pavement, water retaining pavement. Roof cover materials that reduce Urban Heat Island are Cool Roof and Green Roof. The design and toughness of materials should be considered to reduce UHI. Keywords: Urban Heat Island, material feature, thermal performance.